Responses of riverbed sediment bacteria to heavy metals: Integrated evaluation based on bacterial density, activity and community structure under well-controlled sequencing batch incubation conditions. (1st March 2018) - Du, Haixia; Harata, Nobuo; Li, Fusheng
Abstract: Better understanding the responses of riverbed sediment bacteria to heavy metals is a key for considering using riverbed sediment bacterial community as an indicator of river water contamination by heavy metals. For this, integrated evaluation based on bacterial density, activity and community structure through incubation experiments under well-controlled conditions is necessary to obtain more closely relevant findings that are difficult to achieve through field studies. The findings may also include those that can serve as new evidence to clarify contrary findings reported in previous studies. In this study, sequencing batch incubation experiments were performed using sediment suspensions from three rivers with catchment of different land covers and uses. The effects of four metals (Pb, Cr, Cd and Cu) were investigated by spiking them separately under three different concentration levels. Glucose was added once every day as the carbon source throughout the whole incubation lasted for 30 days. The changing trends of the density of general and heterotrophic bacteria showed clearly that the responses of sediment bacteria to Cu were obviously stronger, followed by that to Cd; whereas, the responses to Pb and Cr were not apparent. For incubation with Cu, a short-term inhibition effect appeared in the initial 3 days and was then followed by a long-term promotion effect reflected by obvious increases of bacterial density against control. In regard of bacterial activity evaluated based on the first-order consumption rate for glucose, a trend of decreases was revealed. The results of PCR-DGGE and sequence analysis of extracted 16S rDNA further suggested there were bacterial species that had strong tolerance against the metal and could grow readily to become new dominating ones. The existence of such bacterial species was inferred as the reason leading to the observed increases of bacterial density during incubation with the metal. Graphical abstract: Highlights: New evidences clarifying reported contrary findings in field studies are obtained. Long-term promotion effect of heavy metals on density of sediment bacteria exists. Long-term reduction of overall bacterial activity for glucose uptake is shown. Bacterial species whose growth can be promoted by heavy metals exist. The responses of bacteria to metals follow the order Cu > Cd > Pb & Cr.